63. THE DEVELOPMENT AND PILOT CLINICAL STUDIES OF NON-INVASIVE CAPACITY SCREENING (NICS) ASSAY. (August 2019) - Lu, S.; Yaox, S.; Cai, L.; Wang, X.; Racowsky, C.
Abstract : Introduction: For investigating the detection success rate and accuracy of non-invasive capacity screening(NICS) and determining its effectiveness on improvement of embryo transfer, we reviewed the research results and clinical advances of MALBAC-based NICS from multiple groups worldwide between 2016 to 2018. Material and Methods: 1. Detection success rate: qPCR was used to investigate the starting DNA amount limit and the detection success rate of NICS in 1483 culture medium samples. 2. Detection accuracy 246 embryos with morphological scoring over CC were collected. Culture medium samples were subjected to NICS and the results were compared with whole embryo's aneuploidy results to evaluate the accuracy of NICS as an option of pre-implantation chromosome screening. Also, NICS were applied to 41 families with chromosome translocations to determine its accuracy on pre-implantation chromosome diagnosis. 3. Clinical validation MCT: 120 patients were enrolled and RCT were implemented for non-inferiority comparison of clinical outcomes between NICS and PGS. And 72 patients were recruited for superiority study by comparing clinical outcomes between traditional morphology assessment and NICS. Results: 1. The overall success rate reached to 94.6% among all 1483 culture medium samples with NICS and it mounted to 99.2% when DNA amount ≥ 3pg. 2. The NPV of NICS were over 90% during pre-implantation chromosome screening and this value reached to 97% when applying NICS to pre-implantation chromosome diagnosis. The other performances of NICS including sensitivity, specificity, PPV were comparable to PGS. 3. The clinical results of NICS and PGS from 120 patients did not exhibit significant differences. The clinical outcomes of 72 cases showed that the miscarriage rate of NICS is 0%, and the results are still updating. Conclusions: NICS is a novel genetic testing that allows an accurate selection of blastocysts with better developmental potential for transfer and might improve the clinical outcomes.